Ethics and deontology in medical psychology - Khrol Natalia (Psychiatry, Neurology and Medical Psychology, 2022)
Abstract. The sphere of influence of medical psychology is constantly expanding, which is due to the relevance of mental health problems for modern society and the presence of social demand for psychological assistance. Ethics in medical psychology as one of the types of professional ethics is a set of principles of regulation and norms of behavior of medical psychologists and physicians, determined by the specifics of their activities and the role and position they occupy in society. The concept of medical deontology also includes the system of relationships established in the course of treatment between a doctor and a patient, a medical psychologist and a patient. Deontology is the study of the proper behavior of medical personnel. The subject of deontology in medical psychology is the principles of proper attitude not only towards an individual but also towards society. Referring to the ethical aspects of medical psychology, the modern models of medical ethics are analyzed: the Hippocratic model (V-IV centuries BC) – the key principle of which is: "Do no harm"; the model of Paracelsus (XV-XVI centuries) – the principle of "Do good". This model implements paternalism (pater) as a type of relationship between a medical psychologist and a patient, characterized by positive psychological attachments and social and moral responsibility, "healing", "divinity" of the contact between a medical psychologist and a patient; deontological model (XVIII-XIX centuries) is a set of "proper" rules that correspond to a particular field of medical practice; biomedical ethical model (60-70s of the XX century) considers medicine in the context of human rights. It has been established that medical psychology in all its sections is based on general medical ethical principles. Medical psychologists face specific ethical issues in their work. This is the question of the need to inform the subject about the purpose and content of the psychological examination before it is conducted. Secondly, a medical psychologist must adhere to the rule of "boundaries" (the limit of acceptable behavior). Given the specifics of interpersonal interaction between a medical psychologist and a patient, it is necessary to clearly define professional boundaries of communication during psychological counseling and psychotherapeutic meetings. Thirdly, the formation of emotional attachment of the patient to the medical psychologist, which is one of the characteristics of professional interpersonal interaction, can be a difficult ethical issue. Therefore, a medical psychologist should control the interaction with the patient, being aware of their professional actions, so that emotional support does not interfere with providing the patient with the means to independently cope with difficulties and realize their life goals.